2021
DOI: 10.25259/sni_268_2021
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosis of “White Cord Syndrome” following posterior cervical surgery for ossification of the posterior longitudinal ligament: A case report

Abstract: Background: Following decompressive cervical surgery for significant spinal cord compression/myelopathy, patients may rarely develop the “White Cord Syndrome (WCS).” This acute postoperative reperfusion injury is characterized on T2W MRI images by an increased intramedullary cord signal. However, it is a diagnosis of exclusion, and WCS can only be invoked once all other etiologies for cord injury have been ruled out. Case Description: A 49-year-old male, 3 days following a C3-C7 cervical laminectomy and C2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Subsequently, the phospholipid membranes of neurons are damaged by the generation of such free radicals. 7 From a radiological perspective, white cord syndrome is characterized by a new hyperintense lesion on T2WI in the previously compressed spinal cord. This hyperintensity is usually detected through an MRI scan following the decompressive surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the phospholipid membranes of neurons are damaged by the generation of such free radicals. 7 From a radiological perspective, white cord syndrome is characterized by a new hyperintense lesion on T2WI in the previously compressed spinal cord. This hyperintensity is usually detected through an MRI scan following the decompressive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the phospholipid membranes of neurons are damaged by the generation of such free radicals. 7…”
Section: Discussionmentioning
confidence: 99%
“…[5,6,[8][9][10]12] A newly developed neurological deficit that may be attributed to an intraoperative iatrogenic cord injury is not WCS. Acharya et al reported a case of quadriplegia following cervical posterior decompression surgery that had been caused by an intraoperative iatrogenic spinal cord injury, and WCS was misdiagnosed [17]. WCS is defined as an obvious postoperative motor neuropathy with an unexpected cause.…”
Section: Table 1: Demographics and Clinical Characteristics Of Other ...mentioning
confidence: 99%